Subcooled water flow boiling heat transfer in screw cooling tubes under one-sided heating conditions. (25th February 2017) - Liu, P.; Peng, X.B.; Song, Y.T.; Mao, X.
Highlights: Effectively simulation of the Eulerian multiphase model in subcooled boiling. An analysis of postponing the rise of wall temperature in the screw tubes. An analysis of swirl flow and secondary vortex in screw tube. An analysis of pressure drops of the screw tube was carried out. Abstract: Subcooled flow boiling heat transfer in vertically upward screw cooling tubes was numerically simulated in the paper under one-sided high heat fluxes up to 20 MW/m 2 by using the Fluent software. The Eulerian multiphase model coupled with Non-equilibrium Boiling model was dedicated to explaining the thermal and hydrodynamic characteristics of subcooled flow boiling. A solution algorithm of finite volume discretization was presented to solve the Euler equations. The numerical models were effective for predicting the subcooled water flow boiling heat transfer in the screw tube. Finally, the wall temperature of the interface between the CuCrZr component and the fluid, the pathlines of the fluid, the three components' temperatures, the pressure drops and vapor void fraction were simulated and analyzed. The heat transfer performance of screw tubes was compared with smooth tubes and tubes with twisted tape inserts. The simulated results were as follows: Compared with smooth tubes, the swirl flow and secondary vortex in the screw cooling tube could enhance the turbulence intensity of the fluid and postpone the rise of wall temperatures. The heat transfer performance of the tube with twisted tape inserts was a bit higher than that of the screw tube. In order to avoid the meltdown or destruction under the high heat flux, the screw tube and the tube with twisted tape inserts can sustain 10 MW/m 2 heat flux while the smooth cooling tube can sustain 6 MW/m 2 heat flux.